Simultaneous selection of peach rootstocks by mixed models - Santana, Alice; Uberti, Alison; Rocha, João Romero; Lugaresi, Adriana; Mayer, Newton Alex; Giacobbo, Clevison Luiz (Comunicata Scientiae, 2020)
The term adaptability refers to the ability of a genotype to respond favorably to environmental spur, while stability is the predictability of genotypic behavior. Therefore, the objective was to select Prunus rootstock cultivars with greater adaptability and genotypic stability for subtropical environmental conditions using the HMPRVG method. The experiment was conducted in Chapecó, Santa Catarina State, Brazil. Twenty-one rootstock genotypes were evaluated under the ‘BRS-Libra’ canopy cultivar and one genotype from self-rooted seedlings. The 22 genotypes were evaluated for canopy volume, yield, fruit diameter and fruit set in the growing seasons 2015/16, 2016/17, 2017/18 and 2018/19. Adaptability and stability were measured by means of the harmonic mean relative performance of genotypic values (HMRPGV). In addition, genetic parameters for heritability and ratio test were measured. According to the results, the self-rooted, ‘De Guia’, ‘I-67-52-4’, ‘Mexico Row 1’ and ‘Rosaflor’ genotypes coincided most frequently in the ranking of the three most adaptable and stable genotypes. On the other hand, the ‘P. mandshurica’, ‘Rigitano’ and ‘Santa Rosa’ genotypes corresponded to the lowest adaptability and stability values, thus constituting low quality genetic materials for cultivation. It can be concluded that under the tested conditions the HMPRVG method is efficient for the Prunus rootstock selection cultivars and the ‘BRS-Libra’ grafted on ‘Mexico Row 1’, ‘Rosaflor’ rootstocks and trees from self-rooted seedlings have greater adaptability and phenotypic stability under the subtropical cultivation conditions.